Praktik Pemberian Makan dan Status Gizi Balita di Masa Pandemi Covid 19 : Praktik Pemberian Makan dan Status Gizi Balita di Masa Pandemi Covid 19 - Salma Rasyidah; Anugrah Novianti; Dudung Angkasa; Idrus Jus'at; Harna (Universitas Airlangga, 2022)
Background: Nutritional problems in children under five in Indonesia, such as stunting, obesity, and wasting, are still nutritional problems that are a concern to be addressed, especially during this Covid-19 pandemic. There are limitations in several ways, including access to get healthy food. These influences mothers' feeding practices to fulfill their children's needs less to fulfilled. The feeding practiced to children under five is one of the indirect factors which changes in nutritional status. Objectives: To identify the association between feeding practices and the nutritional status children under five during the Covid-19 pandemic. Methods: The research design was using cross-sectional with a sample of 57 respondents of mothers with children 3-5 years old in Cikupa Health Center Tangerang District. Feeding practice data using the CFPQ (Comprehensive Feeding Practice Questionnaire) from 12 aspects of feeding practiced characteristics there are giving pressure when eating, limitations food for controlling body weight, using food for rewards, using food for controlling children's emotions, limitations food for healthy, controlling children eating behavior, education about food nutrition, encourage children eating variations and balanced food, using the healthy environment for eating healthy at home, influence children for planning and serving food, monitoring children intake, and giving the example of good and right eating and for the nutritional status data using the Z-score indicators of weight for age, height for age, and weight for height. For bivariate analysis using Spearman rho correlation. Results: The results of the analysis using Spearman rho correlation showed there is a positive relationship between feeding practices where mothers involved children in meal planning and nutritional status of weight for age (p=0,019; r=0,3116), monitoring intake and nutritional status of height for age (p=0,005; r=0,366), encouraging varied and balanced children's food intake in weight for height (p=0,012; r=0,331). Conclusion: Feeding practice with aspect of involving children in meal planning, a monitoring children intake and encouraging varied and balanced diet of children has a positive relationship with children nutritional status changes in pandemic Covid-19.